Relationship of Atmospheric Nitrogen Deposition to Soil Nitrogen Cycling Along an Elevation Gradient in the Colorado Front Range - Deborah A. Repert; Ruth C. Heindel; Sheila F. Murphy; Kaitlyn M. Jeanis (Earth's Future)
Abstract Microbial processing of atmospheric nitrogen (N) deposition regulates the retention and mobilization of N in soils, with important implications for water quality. Understanding the links between N deposition, microbial communities, N transformations, and water quality is critical as N deposition shifts toward reduced N and remains persistently high in many regions. Here, we investigated these connections along an elevation transect in the Colorado Front Range. Although rates of N deposition and pools of extractable N increased down the elevation transect, soil microbial communities and N transformation rates did not follow clear elevational patterns. The subalpine microbial community was distinct, corresponding to a high C:N ratio and low pH, while the microbial communities at the lower elevation sites were all very similar. Net nitrification, mineralization, and nitrification potential rates were highest at the Plains (1,700 m) and Montane (2,527 m) sites, suggesting that these ecosystems mobilize N. In contrast, the net immobilization of N observed at the Foothills (1,978 m) and Subalpine (3,015 m) sites suggests that these ecosystems retain N deposition. The contrast in N transformation rates between the plains and foothills, both of which receive elevated N deposition, may be due to spatial heterogeneity not captured in this study and warrants further investigation. Stream N concentrations from the subalpine to the foothills were consistently low, indicating that these soils are currently able to process and retain N deposition, but this may be disrupted if drought, wildfire, or land‐use change alter the ability of the soils to retain N.